Morbidade materna grave e near miss materno no Brasil: revisão sistemática - Silva, Josy Maria de Pinho da (Niterói, 2017)
Submitted by Ana Lúcia Torres (bfmhuap@gmail.com) on 2017-11-13T14:19:06Z No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) Dissertacao Josy Pinho.pdf: 1226133 bytes, checksum: eb4114659ac7eea459d334e4f15bb04f (MD5) === Approved for entry into archive by Ana Lúcia Torres (bfmhuap@gmail.com) on 2017-11-13T14:19:16Z (GMT) No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) Dissertacao Josy Pinho.pdf: 1226133 bytes, checksum: eb4114659ac7eea459d334e4f15bb04f (MD5) === Made available in DSpace on 2017-11-13T14:19:16Z (GMT). No. of bitstreams: 2 license_rdf: 0 bytes, checksum: d41d8cd98f00b204e9800998ecf8427e (MD5) Dissertacao Josy Pinho.pdf: 1226133 bytes, checksum: eb4114659ac7eea459d334e4f15bb04f (MD5) Previous issue date: 2017 === Viva Rio === Objetivo: Análise da morbidade materna grave (near miss materno), por meio de revisão sistemática de estudos no Brasil. Métodos: Foram examinados estudos que relataram dados quantitativos, causas e fatores associados à morbidade materna grave (near miss materno). A busca foi feita pelos sites MEDLINE e LILACS, sendo as palavras-chave: maternal near miss or severe maternal morbidity and Brazil. Foram extraídos dados utilizando-se um protocolo pré-definido (autor, ano, desenho do estudo, população estudada, cenário e contexto, análise estatística, critérios de near miss e resultados). A razão de near miss e os indicadores derivados foram descritos ou estimados, quando não relatados. Resultados: Identificamos 55 estudos, a maioria de desenho transversal (32). Predominaram estudos (40) de base hospitalar (local ou nacional); outros usaram sistemas de informação de saúde ou pesquisas nacionais de saúde. Diferentes definições e terminologias para “near miss” foram adotadas. A Razão de near miss materno variou de 2,4/ 1000 NV a 188,4/ 1000 NV, dependendo dos critérios e do cenário epidemiológico. O índice de mortalidade near miss materno variou entre 3,3% e 32,2%. Doenças hipertensivas e hemorrágicas foram as morbidades mais comuns. As causas indiretas vêm aumentando nos últimos anos. A ausência de cuidados pré-natais e outras demoras nos cuidados de saúde foram associados ao near miss, como também fatores sociodemográficos (cor da pele não branca, adolescência/ idade≥35 anos, baixo nível de escolaridade). Conclusão: O near miss materno no Brasil está associado a iniquidades e demoras na assistência à saúde. Existem grandes diferenças entre as regiões e de acordo com a classificação/ definição usada nos estudos. Os casos de near miss devem ser monitorados rotineiramente em unidades de saúde. Pesquisas futuras sobre casos de near miss materno devem usar os critérios da OMS e expandir o conceito de morbidade materna === Objective: Analysis of severe maternal morbidity (maternal near miss), through systematic review of studies in Brazil. Methods: We examined studies that reported quantitative data, causes, and associated factors on severe maternal morbidity (maternal near miss). The search was through MEDLINE and LILACS, and keywords were: maternal near miss or severe maternal morbidity and Brazil. We extracted data, using a pre-defined protocol (author, year, study design, population studied, setting and context, statistical analysis, criteria of near miss, and results). Near miss ratios, and near miss indicators were described or estimated, when not reported. Results: We identified 55 studies, mainly cross-sectional (32). Most of them (35) were health facility-based (local or national); others used health information systems or national health surveys. Different definitions and terminologies for maternal near miss were adopted. Near miss ratio ranged from 2,4/1000 LB to 188,4/1000 LB, depending on criteria and epidemiological scenario. Mortality index for maternal near miss ranged from 3.3%-32.2%. Hypertensive diseases and hemorrhage were the commonest morbidities. Indirect causes have been increasing in last years. Absence of prenatal care and other delays in health care were associated with near miss, as sociodemographic factors (skin color, adolescence and age > 35 years, low educational level). Conclusion: Maternal near miss in Brazil is associated with health iniquities and delays in health care. Large differences exist between regions and depending on the classification/setting of the studies. Near miss cases should be surveyed routinely in health facilities. Future research on maternal near misses should use WHO criteria and expand the concept of maternal morbidity